2007
DOI: 10.1021/jm061142s
|View full text |Cite
|
Sign up to set email alerts
|

Highly Potent Triazole-Based Tubulin Polymerization Inhibitors

Abstract: We describe the synthesis and biological evaluation of a series of tubulin polymerization inhibitors that contain the 1,2,4-triazole ring to retain the bioactive configuration afforded by the cis double bond in combretastatin A-4 (CA-4). Several of the subject compounds exhibited potent tubulin polymerization inhibitory activity as well as cytotoxicity against a variety of cancer cells including multi-drug-resistant (MDR) cancer cell lines. Attachment of the N-methyl-5-indolyl moiety to the 1,2,4-triazole core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(77 citation statements)
references
References 41 publications
(78 reference statements)
3
74
0
Order By: Relevance
“…Due to its structural simplicity, ease of synthesis, and potent antitumor activity, this class of molecules is widely studied to find potent anticancer agents. [11][12][13] Recently, conjugates bearing imidazo [2,1-b]thiazole scaffolds have become of interest due to their broad spectrum of pharmacological activities, such as antifungal, [14,15] antibacterial, [16][17][18] anti-inflammatory, [19] and antihypertensive properties. [20] It has been reported that they possess antitumor properties against a variety of human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its structural simplicity, ease of synthesis, and potent antitumor activity, this class of molecules is widely studied to find potent anticancer agents. [11][12][13] Recently, conjugates bearing imidazo [2,1-b]thiazole scaffolds have become of interest due to their broad spectrum of pharmacological activities, such as antifungal, [14,15] antibacterial, [16][17][18] anti-inflammatory, [19] and antihypertensive properties. [20] It has been reported that they possess antitumor properties against a variety of human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…This mostly included either modification of the olefinic bond by the introduction of saturation, substituents and other functionalities or its replacement with a three to six membered ring system, which resulted in cis restricted analogues of CA4. 16,[19][20][21][22] Similar to CA4, a number of colchicine site binding ligands are known to inhibit tubulin polymerization and are considered as potential lead like molecules. One of them, E7010 is the first orally active antimitotic sulphonamide derivative that has received much interest in recent years and currently it is in clinical trials.…”
mentioning
confidence: 99%
“…Their cyclization with carbonyl compounds is one of the most important pathways to access 1,2,4-triazole derivatives [46][47][48].…”
Section: Amidrazonesmentioning
confidence: 99%